First Outcomes of Implementing the New Model of Continuous Education in the System of Further Post-Graduate Training of Doctors - Chesnokova, Irina Vladimirovna (Razvitie obrazovaniâ (Online), 2020)
The article is devoted to the consideration of the continuing medical education (CME), which is a supplementary vocational education carried out through the implementation of qualification and further post-graduate training programs. The basic principles of the CME development in the Russian Federation are defined in the article. Among them: continuity in post-graduate training; harmonization with international standards; partnership of the state and professional organizations; comprehensive training of medical workers, that is convenient for them; the use of innovative technologies; quality control and independence, the motivation of employees to improve their skills. During the study the following methods were applied: analysis, comparison and observation. The author of the article outlines that the current regulatory framework for the CME development is the federal laws in the field of healthcare. The results of the study. The majority of doctors accepted a new model as a principal one and registered at the CME website for training. It is concluded that the fundamental difference between the new educational model and the traditional one is that in the СME system an individual 5-year cycle educational plan is drawn up, including 250 credits (hours) of educational activity, which are evenly divided into 50 credits (hours) annually. It is also stated that during the process of implementing the model, certain problems arose: a significant increase in the number of students per year, the increase in the number of organizations accredited for training since it is difficult to control it at the first stage. The СME model needs to be improved and developed, relying on all the best achievements and developments of the traditional system of post-graduate training of doctors.